Associations between cognitive impairment and patient‐reported measures of physical/mental functioning in older people living with HIV1. Issue 5 (26th October 2016) - Underwood, J; De Francesco, D; Post, FA; Vera, JH; Williams, I; Boffito, M; Mallon, PW; Anderson, J; Sachikonye, M; Sabin, C; Winston, A
Abstract : Objectives: While cognitive impairment is frequently reported in HIV‐positive individuals and has historically been associated with poorer functional outcomes, the associations between cognitive impairment and patient‐reported outcome measures (PROMs) in contemporary cohorts are unclear. Methods: We tested cognitive function using a computerized battery (CogState ™ ) in 290 HIV‐positive and 97 HIV‐negative individuals aged ≥ 50 years participating in the Pharmacokinetic and Clinical Observations in People Over Fifty (POPPY) study. Participants completed questionnaires detailing physical and mental health [Short Form Health Survey (SF‐36)], cognitive function [European AIDS Clinical Society (EACS) questions], activities of daily living [Lawton Instrumental Activities of Daily Living (IADL)], depression [Patient Depression Questionnaire (PHQ‐9) and Centres for Epidemiologic Studies Depression scale (CES‐D)], falls and sexual desire. Cognitive impairment was defined using the Frascati criteria, global deficit score (GDS) and multivariate normative comparison (MNC). In the HIV‐positive group, the classification performances of the different definitions of cognitive impairment and dichotomized questionnaire results were calculated. Results: The prevalence of cognitive impairment in the HIV‐positive group was 34.5% (GDS), 30.0% (Frascati) and 22.1% (MNC), with only 2% diagnosed with HIV‐associated dementia. In general, the associations between cognitive impairment and PROMs were weak regardless of the definition used: mean c‐statistics were 0.543 (GDS), 0.530 (MNC) and 0.519 (Frascati). Associations were similar using the global T‐score to define cognitive impairment. Summary health scores (SF‐36) were lower, but only significantly so for those with cognitive impairment identified using MNC, for both mental health (61.4 vs . 75.8; P = 0.03) and physical health (60.9 vs . 75.0; P = 0.03). Conclusions: The associations between cognitive impairment and PROMs were weak, possibly because impairment was mild and therefore largely asymptomatic. Further work is needed to elucidate the clinical implications of cognitive impairment in HIV‐disease.